Classic Cocktails - Reed, Ben (London, United Kingdom : Ryland Peters & Small, 2006)
Aims to provide the inspiration you need to create fabulous cocktails at home. This work presents a collection of recipes, from the delectable Vodkatini to a mouthwatering Bellini.
Where it all began -- Equipment -- Techniques -- Gin -- Vodka -- Whisky -- Rum & Cachaca -- Tequila -- Brandy, Liquers & Aperitifs -- Champagne -- Non-alcoholic
Includes index.
Keywords: COCKTAILS